Bible in the Syriac tradition - Brock, Sebastian P. (Gorgias handbooks, 2020)
This is a basic introduction to the various Syriac translations of the Bible and the ways in which they were used in the Syriac tradition. This new edition has been brought up to date and the bibliography expanded